REKAYASA TEKNOLOGI WORKSHOP PERENCANAAN PARTISIPATIF DENGAN BUSINESS MODEL CANVAS DALAM UPAYA PEMBERDAYAAN PEREMPUAN RAWAN SOSIAL EKONOMI DI YAYASAN USAHA MULIA CIPANAS KABUPATEN CIANJUR - Santika, Sandi; Marwanti, Theresia Martina; Kardeti, Denti (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Families led by women tend to experience higher poverty rates than families led by men. This problem occurs because of the double burden, between earning a living and taking care of the household. Empowered female heads of households have the ability to create economic progress, one of which is by planning joint business groups. This study aims to develop a participatory planning workshop design with a business model canvas (BMC) in an effort to empower Socioeconomically Vulnerable Women (PRSE). The research location is at the Yayasan Usaha Mulia (YUM) Cipanas, Cianjur Regency. This study uses a qualitative method with a Participatory Action Research (PAR) approach. The research subjects consisted of the target group, namely PRSE and the interest group, namely the administrators and social workers at YUM. The research informants were 8 people determined by purposive sampling. Data collection was carried out through in-depth interviews, observations, documentation studies, and Focus Group Discussions (FGD). Data analysis used the Miles and Huberman model. The results of the study showed that the initial design of the workshop implemented by YUM did not answer the needs of the community. Therefore, this study developed it based on needs. After being implemented, the results showed that the design of the participatory planning workshop with the developed BMC could improve PRSE empowerment. This was indicated by the results of the pretest posttest and reflection results which showed an increase in PRSE knowledge about entrepreneurship and as a group were able to implement BMC tools. BMC is a canvas or image to make it easier to see the picture of entrepreneurial ideas. Based on this, the engineering of participatory planning workshop technology with BMC has a positive impact on PRSE empowerment.